KNOWLEDGE AND PRACTICE OF E-WASTE MANAGEMNT AMONG COLLEGE STUDENTS IN WEST BENGAL, INDIA - Chatterjee, Arpita (International Journal of Psychosocial Rehabilitation, 2020)
The present investigation was aimed to understand the knowledge of the college students towards e-waste, and their active participation in sustainable use and management of e-waste. In modern world, everyday varieties of electronic goods are advancing with advancement of technologies. The older versions become obsolete, old fashioned, broken and thus surplus or of no use. This causes an increase burden of electronic wastes, a burning problem for disposal of electronic waste or e-waste throughout the world. The environment and human health are most vulnerable part, which are highly affected by the growing size of e-waste. The objective of the study is to encourage the students in recycling, reduce of excessive use and practice of sustainability of e-waste for effective management of e-waste. For this, a survey was conducted, with both under-graduate and post-graduate students of different colleges of West Bengal, India. The information of knowledge included knowledge on the types of e-waste, effect of e-waste on environment and health, and knowledge on the types of management strategies. For the information of practice of e-waste management, the data collected were participation of respondents in awareness programs of e-waste management, involvement of the participants in recycling of e-waste, training on the e-waste management. In this study it was found that though majority of the respondents had very good- good average knowledge on the types of e-waste and their effect on the environment, but they lack knowledge on the effect of e-waste on health. In case of health perspective, the respondents had poor-very poor knowledge on health hazards caused by the e-waste. Further, the majority of the respondents had poor-very poor knowledge on the management strategies needed for e-waste. Majority of the respondents participated in the awareness programs for e-waste managements few times in life or never participated in such events. Very few participants were directly involved in the recycling of the e-waste in the way of recycling of their mobile phones, pagers, i-pods, computers, and computer related parts, home appliances, etc. As very few of the respondents had proper practical training on the e-waste management, the research was aimed to study their subjective knowledge or theoretical knowledge on the e-waste management in this respect. Data revealed that among the untrained respondents, majority of the respondents had no subjective knowledge also, followed by poor knowledge on the training on E-waste management programs in this regard. The citizens of India more specifically, students are the main segment for e-waste management. They can mobilize the whole society by awareness generation in any new ideas. For this, such type of research is very important to motivate the students. This study was also an effort in this direction.